Cities go at High Speed - Papa, Enrica (TeMA - Journal of Land Use, Mobility and Environment, 2008)
Strategies oriented to the construction of High Speed (HS) transport systems have specific objectives related to a sovra-regional territorial scale: the reduction of long-distance travel time, the increase of accessibility of peripherical areas, Europe integration and social cohesion (European Commission 1991 and 2001; Vicherman 1997). In contrast to these goals, theories and practices demonstrate that HST impacts are more intense and effective at the urban scale (Blum et al. 1997). In fact, HS infrastructures give a stronger transformation potential inside the metropolitan areas and in particular in the stations influence areas, that are connected by the new services and that can be defined as high speed cities. Starting from this hypothesis, this paper investigates the relation between the construction of HST lines and stations and the creation of new “functional urban system” connected by HS services. In particular the article defines a literature framework of HST impacts on urban systems, trough a critical analysis of different approaches and theories. Three main approaches have been investigated: a “regional science” approach, an “activity-based” approach, and an urban design approach, that star from the same hypothesis: HTS services influence directly mobility behaviours. The theories and the empirical research demonstrate the important potential transformations connected by HST infrastructures and services into urban areas.